MODEL PENYERAPAN OBAT UNTUK INTERVAL DAN DOSIS BERBEDA - I NYOMAN WIDANA (Mathematics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2010)
This article will discuss the accumulated quantity of the drug in the bloodstream of the twoadministered methods of the drug. The first method the drug is administered every 12 hours with adose of 12.5 mg, whereas for the second method the drug is administered every 24 hours with a dose of25 mg. The calculations show that the second method accumulates more drugs in the bloodstream thanthe first method.